PENGARUH KNOWLEDGE MANAGEMENT, TECHNOLOGY DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI (Studi Kasus Pegawai Kantor Dinas Lingkungan Hidup Kabupaten Manokwari) - Graselsya Febri Arung Bangalino; Nurwidianto Nurwidianto; Louis Soemadi Bopeng (Cakrawala Management Business Journal, 2019)
In today’s era of competition is important for organization, so expect knowledge management, technology and discipline work can contribute well as human resources, especially in the world of office. This study aims to measure the influence of the knowledge management, technology and work discipline of the employment of the office of the environment office of the Manokwari district. Method of associative research with multiple linear regression analysis technique. The number of samples in this study as many as 46 respondents with sample collection techniques Judgement Sampling. The result of the analysis shows that the knowledge management, technology and work discipline has a significant effect on the performance of the employees of the environment office of the Manokwari district.